Contextual variations in emotion polyregulation: how do regulatory goals shape the use and success of emotion regulation strategies in everyday life? - Hartmann, Steffen; Prüßner, Luise; Barnow, Sven (Emotion, 2023)
Emotion regulation strategies are frequently combined within one emotional episode, a phenomenon labeled emotion polyregulation. Nevertheless, there is a scarcity of studies examining which regulatory strategies are commonly combined across different contexts and how effective these combinations are in everyday life. Targeting this research gap, the present ecological momentary assessment study modeled emotion polyregulation and its success for contexts of (a) downregulation, (b) upregulation, and (c) maintenance goals in N = 321 adults. The endorsement and success of 15 different emotion regulation strategies derived from the process model of emotion regulation were measured 5 times a day for 7 days. Multilevel factor analyses revealed that individuals tend to combine different regulatory strategies depending on the activated regulatory goal: When examining downregulation, four factors best described the combined use of regulatory strategies: Situation Modification, Repetitive Processing, Emotional Avoidance, and Interpersonal Regulation. In contrast, three-factor models characterized emotion polyregulation for upregulation (Emotional Acceptance, Repetitive Processing, and Interpersonal Regulation) and maintenance goals (Unspecific Regulation, Emotional Acceptance, and Interpersonal Regulation). Moreover, multilevel structural equation modeling revealed that the success of emotion polyregulation is goal-dependent. While combining interpersonal and situation modification strategies was related to beneficial outcomes for downregulation goals, acceptance-based strategies were most strongly associated with emotion regulation success in situations of upregulation and maintenance. These results add to a more complex understanding of emotion regulation in daily life and highlight the necessity of broadening the focus of emotion regulation research to examine emotion polyregulation. (PsycInfo Database Record (c) 2023 APA, all rights reserved)
Gesehen am 18.01.2024